Tracer la procéduralisation dans le contexte interactionnel et multimodal d’une classe d’immersion - Nathalie Blanc; Peter Griggs (Recherches en didactique des langues et des cultures)
Content-based language learning in its various forms continues to evolve as a highly effective way of acquiring a second language. This paper adopts a sociocognitive perspective, anchored in the Vygostkyan school of thought and drawing also on the field of cognitive sciences, to explore how second language skills are developed in this learning context through the interplay and the reciprocal structuring of language use and the processing of content knowledge. The study is based on a video corpus of a class of 9 year-old students carrying out a science project in a French Immersion School in Minnesota. In order to trace this process of proceduralisation, we combine quantitative and qualitative methods of analysis. The study focuses on short pre-classified sequences of transcribed video recordings in which prototypical constructions are recycled in different multimodal discourse contexts. Then, drawing on techniques of discourse and conversational analysis, the study explores more deeply how the interplay between the multimodal components of the different discourse settings contributes to the development of language skills.